2022
DOI: 10.3390/ijerph19074173
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Effectiveness of Telemedicine in Glycemic Management among Patients with Type 2 Diabetes in Primary Care

Abstract: Introduction: Telemedicine interventions are gradually being used in primary health care to help patients with type 2 diabetes receive ongoing medical guidance. The purpose of this study was to analyze the effectiveness of using telemedicine in primary health care for the management of patients with type 2 diabetes. Methods: A systematic search was conducted from database inception to August 2021 in nine databases, including PubMed, Web of Science, Cochrane Library, EMBASE, EBSCO, CNKI, Wanfang Data, VIP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 72 publications
(228 reference statements)
3
14
1
2
Order By: Relevance
“…A meta-analysis of 32 articles on telemedicine in primary healthcare for the management of patients with Type 2 diabetes demonstrated that telemedicine had a favourable effect on diabetes care. 2 Holt described the outcomes of the study, which showed that telemedicine interventions may help patients with Type 2 diabetes to effectively control blood glucose and improve self-management in primary healthcare. The analysis showed that telemedicine leads to a reduction in HbA1c, a reduction in fasting and postprandial glucose, and reduction in blood pressure.…”
Section: How Effective Is Telemedicine In Diabetes Care?mentioning
confidence: 99%
“…A meta-analysis of 32 articles on telemedicine in primary healthcare for the management of patients with Type 2 diabetes demonstrated that telemedicine had a favourable effect on diabetes care. 2 Holt described the outcomes of the study, which showed that telemedicine interventions may help patients with Type 2 diabetes to effectively control blood glucose and improve self-management in primary healthcare. The analysis showed that telemedicine leads to a reduction in HbA1c, a reduction in fasting and postprandial glucose, and reduction in blood pressure.…”
Section: How Effective Is Telemedicine In Diabetes Care?mentioning
confidence: 99%
“…Sobre o nível de escolaridade, a maioria (22) cursava o Ensino Fundamental II (6º a 9º ano); seguido de 34% (17) no Ensino Fundamental I (1º ao 5 ano); (7) no ensino médio (1º ao 3º) e apenas (2) na Educação Infantil. A maior procedência era de crianças e adolescentes advindas do interior do Estado do Ceará 50% (25); seguidos dos moradores da capital 38% (19) e, apenas 12% (6) da Região Metropolitana, como visto na tabela 1 abaixo.…”
Section: Recima21 -Revista Científica Multidisciplinar Issn 2675-6218...unclassified
“…Há evidências na literatura científica que apontam resultados promissores sobre o uso da Telessaúde como um aumento expressivo da utilização dessa ferramenta digital durante a pandemia, o que favoreceu para limitação do contato das pessoas e contribuindo para a redução da transmissão viral 22 .…”
Section: Recima21 -Revista Científica Multidisciplinar Issn 2675-6218...unclassified
“…Telehealth has the potential to improve access to and quality of care for low-income patients with chronic conditions such as diabetes [1][2][3][4]. This includes patients served by federally qualified health centers (FQHCs), which provide comprehensive primary and preventive care services to millions of low-income patients across the United States.…”
Section: Introductionmentioning
confidence: 99%